Development & application of solar induced ventilation prototype for Small and Medium Enterprise (SME) building - Sapian, Abdul Razak; Mohammad Yusoff, Wardah Fatimah; Adam, Nor Mariah (2012)
The use of solar energy in solar induced ventilation helps to enhance the stack ventilation which is normally less efficient in the hot humid climate due to the small temperature difference between the inside and outside of naturally-ventilated buildings. Therefore development and application of solar induced ventilation prototype in industrial building, particularly the premises of small and medium enterprises (SMEs) is crucial. The development and application of this strategy in SME premises is expected to promote natural ventilation, hence reducing the business operating cost. Moreover, high ventilation rates are necessary to such building in maintaining healthy indoor air quality.